Giant Gastric Bezoar Complicating Congenital Esophageal Atresia Repaired by Gastric Interposition—A Case Report - Chacko, Archana; Masters, Brent I.; Isles, Alan (Frontiers in Pediatrics, 2017)
We describe a giant gastric phytobezoar in a child with repaired congenital oesophageal atresia. At age two, a gastric interposition (pull-up) procedure was performed for severe and recurrent oesophageal strictures. For twelve months post-gastric interposition, he experienced frequent respiratory illnesses requiring hospital admissions but it was not initially appreciated that these episodes were likely secondary to recurrent aspiration from a gastric bezoar with“spill-over” aspiration.